The Effectiveness and Safety of Convalescent Plasma as a Therapy for COVID-19 Patients: A Literature Review - Tri Setyawati1, Virgiana2, Rosa Dwi Wahyuni3, Sumarni3, Rosmala Nur3 (Institute of Medico-legal Publications Pvt Ltd, 2020)
COVID-19 is a new disease caused by SARS-CoV-2 with an increasing number of cases. until now, no specificvaccine or antiviral therapy regimen has yet been found. A therapy that has been known for approximately acentury ago called convalescent plasma therapy has been discussed again as an effective and safe therapy forCOVID-19 patients. Conduct a literature review of scientific studies related to the effectiveness and safetyof convalescent plasma as a therapy for COVID-19 patients. Convalescent plasma has proven to be effectivebecause it can improve the clinical condition felt by patient, prevent the entry of viruses into cells and inhibitthe virus replication. This therapy is also proven to have no harmful effects, so it is safe to be performed bypaying attention to certain things such as conditions that must be fulfilled by the donors.